Giardia duodenalis in the Philippines: A Review of Prevalence, Epidemiology, and Diagnostic and Treatment Challenges - Quidato, Clark Jan J.; Jr., Nicolas G. Guanzon; Jr., Rolando V. Pakingking (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Giardia duodenalis, commonly referred to as Giardia intestinalis or Giardia lamblia, is a worldwide relevant protozoan parasite responsible for giardiasis, a gastrointestinal disorder. Giardiasis continues to pose a public health challenge in the Philippines, especially in areas with inadequate sanitation and hygiene. Prevalence rates differ nationwide, with elevated infection rates observed in children, institutionalized groups, and regions with restricted access to clean water. Assemblage B, the predominant genotype identified, underscores the danger of zoonotic transmission. Notwithstanding progress in molecular diagnoses, conventional microscopy continues to be the principal diagnostic instrument, limited by resource constraints. Chronic giardiasis leads to malnutrition, development retardation, and cognitive deficits, especially in children from disadvantaged backgrounds. Addressing these deficiencies requires enhanced diagnostic techniques, focused public health initiatives, and investments in water sanitation infrastructure. This review highlights significant research deficiencies and emphasizes the necessity for extensive initiatives to alleviate the impact of giardiasis in the Philippines.